Association between ACTA1 candidate gene and performance, organs and carcass traits in broilers - Venturini, G. C. [UNESP]; Stafuzza, N. B. [UNESP]; Cardoso, D. F. [UNESP]; Baldi, F. [UNESP]; Ledur, M. C.; Peixoto, J. O.; Faro, L El; Munari, D. P. [UNESP] (Poultry Science Association Inc., 2015)
This study investigates the genetic association of the SNP present in the ACTA1 gene with performance traits, organs and carcass of broilers to help marker-assisted selection of a paternal broiler line (TT) from EMBRAPA Swine and Poultry, Brazil. Genetic and phenotypic data of 1,400 broilers for 68 traits related to body performance, organ weights, weight of carcass parts, and yields as a percentage of organs and carcass parts were used. The maximum likelihood method, considering 4 analytical models, was used to analyze the genetic association between the SNP and these important economic traits. The association analysis was performed using a mixed animal model including the random effect of the animal (polygenic), and the fixed effects of sex (2 levels), hatch (5 levels) and SNP (3 levels), besides the random error. The traits significantly associated (P < 0.05) with the SNP were analyzed, along with body weight at 42 days of age (BW42), by the restricted maximum likelihood method using the multi-trait animal model to estimate genetic parameters. The analysis included the residual and additive genetic random effects and the sex-hatch fixed effect. The additive effects of the SNP were associated with breast meat (BMY), liver yield (LIVY), body weight at 35 days of age (BW35); drumstick skin (DSW), drumstick (DW) and breast (BW) weights. The heritability estimates for these traits, in addition to BW42, ranged from 0.24 ± 0.06 to 0.45 ± 0.08 for LIVY and BW35, respectively. The genetic correlation ranged from 0.02 ± 0.18 for LIVY and BMY to 0.97 ± 0.01 for BW35 and BW42. Based on the results of this study, it can be concluded that ACTA1 gene is associated with performance traits BW35, LIV and BMY, DW, BW and DW adjusted for body weight at 42 days of age. Therefore, the ACTA1 gene is an important molecular marker that could be used together with others already described to increase the economically important traits in broilers.
Keywords: Qxpak; Snp; Drumstick yield; Genetic association; Wing weight